A influência da cor no design de interiores - Franck, Adriana Neves Lázaro (2022)
Designing an interior space goes far beyond creating an aesthetically pleasing environment. In fact, beyond the visual result, interior design seeks to find and develop solutions that potentialize the space. Nevertheless, to design an environment is to reflect the personality of those who inhabit it. In the creation of an interior project, there is a factor that influences it's perception - color. Color is constantly present in the world around us. Although it is sometimes seen as something merely decorative, color is an expressive and symbolic element, fundamental in visual language. The human being experiences, interacts and understands the environment through color, which has the power to arouse sensations that influence behavior and well being. This research seeks to understand how the introduction of color in interior space influences spatial perception, and consequently the architectural experience. It aims to understand color, it's symbolism and its ability to influence the reading of space.Given the intrinsic relationship between man and space, it is irrefutable the dimension that both have in interior design, where the ultimate goal is to develop an ideal space that meets the user's needs. Thus, the present project work intends to investigate the relationship between color as a design element, analyzing its effect on the space and on the user, developing a research on the application and complexity of color use, and finally making an interior design as a result of this process.